Assessment of Safety, Effects, and Muscle-Specific Accumulation of Dietary Butylated Hydroxytoluene (BHT) in Paralichthys olivaceus - Seunghan Lee; Min-Gi Kim; Sang-Woo Hur; Kumar Katya; Kang-Woong Kim; Bong-Joo Lee (Aquaculture Nutrition, 2023)
Butylated hydroxytoluene (BHT) is a commonly used antioxidant added to animal/fish feed to limit lipid autoxidation and peroxidation. Although there have been reviews and reports of BHT toxicity in animals, limited information is available with respect to the toxic effects and accumulation of BHT due to oral exposure in aquaculture species. Therefore, 120 days of feeding trial was conducted to evaluate the effects of dietary BHT on the marine fish olive flounder Paralichthys olivaceus. Graded levels of BHT were added to the basal diet in increments of 0, 10, 20, 40, 80, and 160 mg BHT/kg, corresponding to 0 (BHT0), 11 (BHT11), 19 (BHT19), 35 (BHT35), 85 (BHT85), and 121 (BHT121) mg BHT/kg diets, respectively. Fish with an average weight of 77.5±0.3 g (mean±SD) were fed one of the six experimental diets in triplicate groups. Growth performance, feed utilization, and survival rate were not significantly affected by the dietary BHT levels among all experimental groups, whereas BHT concentration in the muscle tissue was found to increase in a dose-dependent manner up to 60 days of the experimental period. Thereafter, BHT accumulation in muscle tissue showed a declining trend among all treatment groups. Furthermore, the whole-body proximate composition, nonspecific immune responses, and hematological parameters (except triglycerides) were not significantly influenced by the dietary levels of BHT. Blood triglyceride content was significantly higher in fish fed the BHT-free diet compared to all other treatment groups. Thus, this study demonstrates that dietary BHT (up to 121 mg/kg) is a safe and effective antioxidant without exhibiting any adverse effects on the growth performance, body composition, and immune responses in the marine fish olive flounder, P. olivaceus.